2009
DOI: 10.1259/dmfr/28859075
|View full text |Cite
|
Sign up to set email alerts
|

Influence of prednisolone-induced osteoporosis on bone mass and bone quality of the mandible in rats

Abstract: These findings suggest that steroid treatment decreases the cortical BMC, bone area and bone strength of the mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…A total of 10 papers investigated the effect of mechanical loading, through diet texture modification and mastication [7], [11], [13], [19], [27], [29], [31], [36], [37], [38] on the bone micro-architecture, while 8 addressed the effect of drug intervention [3], [12], [32], [34], [39], [40], [41], [42]. One paper investigated the mandibular bone architecture in the ovariectomy-induced osteoporotic animal [43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 10 papers investigated the effect of mechanical loading, through diet texture modification and mastication [7], [11], [13], [19], [27], [29], [31], [36], [37], [38] on the bone micro-architecture, while 8 addressed the effect of drug intervention [3], [12], [32], [34], [39], [40], [41], [42]. One paper investigated the mandibular bone architecture in the ovariectomy-induced osteoporotic animal [43].…”
Section: Resultsmentioning
confidence: 99%
“…The literature search also identified 16 reports dealing with interventions which potentially impact the bone micro-architecture and the bone healing or regeneration, with 6 studies applying to the maxilla [3], [4], [8], [15], [16], [23], 6 to the mandible [3], [11], [32], [40], [41], [43] and 4 to the condyle region [10], [22], [28], [46]. It is evident that the control groups included in these studies offer the possibility to extract bone micro-architectural parameters that characterize the physiological bone micro-architectural state.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that long-term GCs administration induced alveolar bone loss in mice; diminished the cortical bone mineral substance, as well as bone area and strength of rats' mandibles (16,17). Likewise, GIOP can potentiate the destructive impacts of experimental periodontitis on the alveolar bone of rats (18).…”
Section: Introductionmentioning
confidence: 99%
“…Among the many effects of glucocorticoids on bone, they are known to suppress PLR in trabecular and cortical bone of the femur, which likely plays a causal role in glucocorticoid-induced osteonecrosis of the femoral head ( Fowler et al, 2017 ). In the mandible, glucocorticoids alter the biomechanical behavior of the bone as well as decrease overall cortical bone mass and strength ( Bozzini et al, 2015 ; Kozai et al, 2009 ). However, the extent to which PLR in the mandible is sensitive to glucocorticoids has yet to be studied.…”
Section: Introductionmentioning
confidence: 99%